2012
DOI: 10.1039/c2cp42705b
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency dye-sensitized solar cells exploiting sponge-like ZnO nanostructures

Abstract: Sponge-like nanostructured ZnO layers were successfully employed as photoanodes for the fabrication of highly efficient dye-sensitized solar cells. The sponge-like ZnO layers were obtained by room temperature radio-frequency magnetron sputtering deposition of metallic zinc, followed by thermal oxidation treatment in an ambient atmosphere. The porous films show a 3D branched nanomorphology, with a feature similar to natural coral. The morphological and optical properties of these layers were studied through fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…Table II compares the performance of the developed ZnO photo-anode (on FTO coated glass substrates) with the other ZnO based dye sensitized solar cell reported recently. 24,28,36,[38][39][40][41][42] For dye sensitized solar cell application, zinc oxide based photo-anode with various dyes and electrolytes has been reported. [29][30][31][32][33][34][35] However, the cells having significant solar to electric conversion efficiency (!2%) and prepared using N3/N719 dyes and I À /I 3 À electrolyte are considered for the present comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Table II compares the performance of the developed ZnO photo-anode (on FTO coated glass substrates) with the other ZnO based dye sensitized solar cell reported recently. 24,28,36,[38][39][40][41][42] For dye sensitized solar cell application, zinc oxide based photo-anode with various dyes and electrolytes has been reported. [29][30][31][32][33][34][35] However, the cells having significant solar to electric conversion efficiency (!2%) and prepared using N3/N719 dyes and I À /I 3 À electrolyte are considered for the present comparison.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of solar energy harvesting, particularly for what concerns DSCs, photoanodes based on porous zinc oxide layers can provide photoconversion efficiencies as high as about 7 % [119,135,136], although TiO 2 -based photoanodes still give the best performances (with efficiencies over 11 % [137]). Many efforts have been dedicated by several research groups to the study of nanostructured ZnO-based DSC photoanodes, since ZnO electronic transport and mobility properties are more favorable to the correct DSC operation than those of TiO 2 , and, in addition, the advantage over TiO 2 , represented by the ease of synthesizing ZnO nanostructures with a variety of shapes, can help tuning such properties [137].…”
Section: Porous Zno Filmsmentioning
confidence: 98%
“…TiO 2 layers with an average thickness of 8 lm were sensitized with N719, soaking them in 0.35 mM ethanol-based dye solution (Ruthenizer 535bis-TBA, Solaronix). Counter electrode fabrication and cell assembly procedures were reported in previous works (Lamberti et al, 2013;Sacco et al, 2012a). Synthetically, to prepare the counter electrodes, FTO-glasses were drilled to create an inlet port for the electrolyte filling, then cleaned as described above and Pt-coated (5 nm) by thermal evaporation.…”
Section: Dsc Fabrication and Characterizationmentioning
confidence: 99%
“…The sealed cells were filled with the electrolyte following a vacuum procedure (Sacco et al, 2012a) and no difference in the filling step was observed by the addiction of the nanoparticles. In Fig.…”
Section: Electrolyte Characterizationmentioning
confidence: 99%